PELAKSANAAN PEMBERIAN BANTUAN HUKUM BAGI PEREMPUAN KORBAN KEKERASAN SEKSUAL - Fitria Hutasuhut, Amanda Rizda; Eka Putra, Mohammad; Rosmalinda, Rosmalinda (Penerbit Lafadz Jaya, 2026)
Sexual violence against women is a form of human rights violation that has a widespread impact on the physical, psychological, social, and legal conditions of victims. In legal protection efforts, the provision of legal aid is an important instrument to ensure that victims' rights to justice and recovery are fulfilled. This study aims to analyse the implementation of legal aid for women victims of sexual violence in Indonesia, as well as to examine the obstacles encountered in practice. The research method used is empirical legal with a regulatory approach, case studies, and interviews with legal aid institutions and victims. The results of the study show that although regulations on legal aid have been stipulated in Law No. 16 of 2011 on Legal Aid and various other implementing regulations, in practice there are still structural and cultural barriers. These obstacles include limited access to information about legal aid services for victims, social stigma, gender inequality in the judicial system, and the limited number of legal aid organisations with the capacity to handle cases of sexual violence specifically. Additionally, many victims experience intimidation and revictimisation during the legal process. This study recommends the need to optimise the role of the state through strengthening regulations, enhancing the capacity of legal aid organisations, and providing gender-responsive support services. There is also a need for synergy between law enforcement agencies, local governments, and civil society organisations to build a comprehensive legal protection system for women victims of sexual violence. Thus, the principles of substantive justice and the fulfilment of victims' rights can be better guaranteed in the legal process in Indonesia.